COMPARING INCLUSIVE EDUCATION IN TURKEY AND ARGENTINA - Orhan Kahya; Vural Hoşgörür (Informascope, 2018)
Comparative Education is a discipline helps to identify the similarities and differences and explains the facts appearing similar between two or more education systems in different cultures and various countries, and puts forward useful suggestions about the ways to educate people (Türkoğlu, 1985). Since Salamanca Statement (UNESCO, 1994), inclusive education has got considerable steps globally. That has made the governments take the action to apply educational policies to eliminate students' disadvantage arising from gender, disability, culture, ethnicity, socio economic background etc. The purpose of this paper is to compare inclusive education in Turkey and Argentina. Bereday's (1964) comparative education model has been conducted through the study. Comparing inclusive education in Turkey and Argentina not only contribute to better understand the inclusive education implications in these two developing countries but also define problems and propose solutions. While inclusive education policies in Turkey focus on disabled students and students with learning difficulties, they focus on disadvantaged groups to provide educational equality.